Studies on the ecology and distribution of zooplankton biomass in kadalur coastal zone, Tamil nadu, India - Enbarasan1, Prabhahar.C1, Saleshrani.K2; R. (Current Botany, 2011)
Zooplankton diversity important criteria for evaluating the suitability of water for irrigation and drinking purposes. In this study, we tried to assess the Zooplankton species richness, diversity, and evenness and to predict the state of three stations. The Zooplankton showed seasonal variations at all the stations. The order of abundance of Zooplankton at the three selected stations are Station 1 (Palar river): Rotifera > Cladocera > Ciliata > Copepoda > Others, Station 2 (Palar estuary):Ã‚Â Ciliata > Siphanophora > Rotifera > Polychaeta > Cladocera > Copepoda > Cirripedia > Others and Station 3 (Kadalur sea coast): Copepoda > Ciliata > Hydrozoa > Rotifera > Amphipoda > Chaetognatha > Cladocera > Others.